The performance of emerging materials derived from waste organism blood and saponified modified orange peel for immobilization of available Cd in soil. Issue 61 (9th October 2020) - HuangFu, Zhuoxi; Ran, Zongxin; Mo, Yinpeng; Xu, Zichen; Wei, Wei; Yu, Jiang; Lai, Bo; Wang, Xingrun
Abstract : In our study, waste organism blood (WOB) and chemically modified orange peel (SOP) were applied to investigate their sorption potential for the immobilization of available Cd in soils. Abstract : Waste organism blood (WOB) and orange peel are emerging stabilization materials obtained as by-products from agricultural processes, which are quite suitable for heavy metal immobilization in soil. In this work, waste organism blood and chemically modified orange peel (SOP) were investigated as potential sorbents for immobilization of available Cd in soil. Application of 5% WOB and SOP effectively immobilized cadmium (Cd) with an associated regulation of soil pH, among which the pH of acidic soil increased most significantly. While the application of 3% SOP alone stabilized almost the same amount of available Cd compared to WOB, it caused the highest stabilization rate of 58.85% when applied at 5%. By contrast, SOP combined with WOB (the mass ratio of the material is 1 : 1) at a 5% addition rate stabilized the available Cd in soils remarkably, with a stabilization rate of 57.74%. This study revealed that the soil particles after stabilization have a more compact and flaky structure, and the SOP and WOB had a particular pore structure, which was helpful for the adsorption of available Cd in soil. This study put forward new insights into the potential effects of Cd immobilization in contaminated soil by newly emerging stabilization biomass materials (WOB and SOP).